ANALYSIS KEBUTUHAN MEDIA PEMBELAJRAN MICRO-LEARNING GAMIFIKASI MENGATASI RENDAHNYA KEMANDIRIAN BELAJAR SISWA KELAS VI SD - Umi Aklakkul Karimah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This research is motivated by the low learning independence of sixth-grade students, characterized by passivity and high dependence on teacher instructions. This condition indicates the need for learning media that are more appropriate to the characteristics of elementary school students in the digital era. The purpose of this study is to analyze the need to develop gamification-based micro-learning media to support the learning independence of sixth-grade elementary school students. This study uses the Research and Development (R&D) method with the ADDIE model, but the scope of the study is limited to the Analysis or needs analysis stage. Data were collected through interviews with educators, classroom learning observations, and the distribution of questionnaires to 18 sixth-grade students. The analysis results show that 78% of students experience difficulties in starting independent learning and are still dependent on teacher direction. In addition, the learning media used is not fully adaptive to the characteristics of digital generation students. The findings also show that 90% of students have access to devices, but their use is more dominant for entertainment than learning activities. Based on the results of the needs analysis, the development of gamification micro-learning media is seen as relevant as an alternative solution to address students' learning needs and serves as the basis for the media design and development stages in the ADDIE model. Thus, this research becomes the initial basis for the design and development stage of learning media that is more appropriate to students' needs. ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya kemandirian belajar siswa kelas VI yang ditandai dengan pasivitas dan ketergantungan tinggi terhadap instruksi guru. Kondisi tersebut menunjukkan perlunya media pembelajaran yang lebih sesuai dengan karakteristik siswa sekolah dasar di era digital. Tujuan penelitian ini adalah menganalisis kebutuhan pengembangan media pembelajaran micro-learning berbasis gamifikasi untuk mendukung kemandirian belajar siswa kelas VI sekolah dasar. Penelitian ini menggunakan metode Research and Development (R&D) dengan model ADDIE, namun ruang lingkup penelitian dibatasi pada tahap Analysis atau analisis kebutuhan. Data dikumpulkan melalui wawancara dengan pendidik, observasi pembelajaran di kelas, dan penyebaran kuesioner kepada 18 siswa kelas VI. Hasil analisis menunjukkan bahwa 78% siswa mengalami kesulitan dalam memulai belajar mandiri dan masih bergantung pada arahan guru. Selain itu, media pembelajaran yang digunakan belum sepenuhnya adaptif terhadap karakteristik siswa generasi digital. Temuan juga menunjukkan bahwa 90% siswa memiliki akses terhadap gawai, tetapi penggunaannya lebih dominan untuk hiburan daripada kegiatan belajar. Berdasarkan hasil analisis kebutuhan, pengembangan media pembelajaran micro-learning gamifikasi dipandang relevan sebagai alternatif solusi untuk menjawab kebutuhan pembelajaran siswa dan menjadi dasar bagi tahapan desain dan pengembangan media pada model ADDIE. Dengan demikian, penelitian ini menjadi dasar awal bagi tahap desain dan pengembangan media pembelajaran yang lebih sesuai dengan kebutuhan siswa.